Limited Wegener's Granulomatosis as a Solitary Pulmonary Nodule - A Case Report (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Limited Wegener`s Granulomatosis (WG) has been infrequently reported from India so far. We report a case of Limited WG in a 60 year old male, who presented to us with productive cough and hemoptysis, and a right upper lobe mass lesion on chest roentgenogram. He was previously treated outside as Pulmonary Koch’s, without any improvement. We diagnosed the patient on histo-pathological examination of right upper lobectomy specimen. He was administered five pulses of intravenous cyclophosphamide therapy plus oral corticosteroids, with significant symptomatic improvement. He was given oral methotrexate and tapering doses of corticosteroids in follow up. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 33-36 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7977